Unbecoming One: Legal Construction of Muslim Family in Indonesia - Hamzić, Vanja (2011)
This project seeks to unearth an astonishing diversity of familial ties and types amongst Indonesian Muslim communities, including those considered illicit or 'irregular' by the state and religious authorities. It traces down and analyses various legislation and policies introduced before and after the country's independence, aimed at strict regulation of 'family nucleus', gender roles and relations. Particular attention is paid to the most recent legal intrusion in Indonesian familial diversity, via state laws and provincial by-laws that regulate sexuality and gender. The theoretical lenses of, inter alia, feminist legal theory and Islamic law are used to provide a springboard for a more comprehensive understanding of the role of state and law in (de/re)construction of the family in Indonesia.